A multi-method approach to constrain the age of eruption and post-depositional processes in a Lower Jurassic ignimbrite from the Marifil Volcanic Complex, eastern North Patagonian Massif - González, Santiago Nicolás (2022)
Fil: González, Santiago. Universidad Nacional de Río Negro, Instituto de Investigación en Paleobiología y Geología. Río Negro, Argentina.